Publiczne wsparcie dla rozwoju energetyki odnawialnej a jej rynkowa efektywność (ze szczególnym uwzględnieniem Unii Europejskiej) - Fiedor, Bogusław (Public Support for Renewable Energy Development and Its Market Efficiency, 2009)
In the introductory part of the paper, the author explains why the energy sector, and its part connected with the production and distribution of electricity and heat in particular, must be a subject to the public regulation. Against this background, in the second part of the paper legal-institutional and economic instruments of public support for renewable energy are presented. This support is also related to the strategic goals of EU energy policy: integration and liberalization of common energy market, energy supply safety, environmental protection and sustainable development of energy sector. Following that, fiscal instruments of public support for renewable energy are discussed in depth. In the final part of the paper, the author attempts to define conditions and mechanisms which meeting and/or implementation might contribute to such an increase in economic and financial efficiency of renewable energy that it could be step by step integrated into the more and more liberal common energy market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 93-110